The Role of Portfolio Constraints in the International Propagation of Shocks - PAVLOVA, ANNA; RIGOBON, ROBERTO (Review of Economic Studies, 2008)
We study the comovement among stock prices and exchange rates in a three-good, three-country, Centre-Periphery, dynamic equilibrium model in which the Centre's agents face portfolio constraints. We characterize equilibrium in closed form for a broad class of portfolio constraints, solving for stock prices, terms of trade, and portfolio holdings. We show that portfolio constraints generate wealth transfers between the Periphery countries and the Centre, which increase the comovement of the stock prices across the Periphery. We associate this excess comovement caused by portfolio constraints with the phenomenon known as contagion. The model generates predictions consistent with other important empirical results such as amplification and flight-to-quality effects.